2002
DOI: 10.1017/s0080440102000142
|View full text |Cite
|
Sign up to set email alerts
|

Topographies of Politeness

Abstract: Politeness was a quintessentially urban concept; the formulation of a code of polite behaviour was a response to the pressures of urban living and the cultivation and display of polite manners took place in the social spaces of the urban locale. Not all towns were equally polite, however, and the degree of politeness on display in a town became another yardstick by which to categorise and judge provincial society. London was often presented as the centre of true politeness, in contrast to provincial vulgarity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Recent research by Jon Stobart and colleagues has found that the actual leisure facilities available in smaller resorts often differed little from those available in other county or commercial towns, 10 yet as he and other urban historians have demonstrated elsewhere, towns were deemed polite or otherwise on the basis of several factors, most importantly physical appearance (clean, paved streets and regular, perhaps neo-classical, buildings), the possession of social institutions such as assemblies, libraries or theatres and the presence of 'good' (i.e., genteel or, ideally, aristocratic) company. 11 As will be seen, the balance with which these criteria were fulfilled in Moffat was uneven: developments in the built environment were slow and piecemeal, the spaces in which polite social activities were performed were limited for much of the century, and the presence of good company was nowhere more ephemeral and reliant on the trends of fashion than in a resort. Moreover, spas faced more specific challenges to refinement.…”
Section: Reputation and Representationmentioning
confidence: 99%
“…Recent research by Jon Stobart and colleagues has found that the actual leisure facilities available in smaller resorts often differed little from those available in other county or commercial towns, 10 yet as he and other urban historians have demonstrated elsewhere, towns were deemed polite or otherwise on the basis of several factors, most importantly physical appearance (clean, paved streets and regular, perhaps neo-classical, buildings), the possession of social institutions such as assemblies, libraries or theatres and the presence of 'good' (i.e., genteel or, ideally, aristocratic) company. 11 As will be seen, the balance with which these criteria were fulfilled in Moffat was uneven: developments in the built environment were slow and piecemeal, the spaces in which polite social activities were performed were limited for much of the century, and the presence of good company was nowhere more ephemeral and reliant on the trends of fashion than in a resort. Moreover, spas faced more specific challenges to refinement.…”
Section: Reputation and Representationmentioning
confidence: 99%
“…59 The kind of rhetoric that portrayed Liverpool as a cultural desert without 'a single erection or endowment, for the advancement of science, the cultivation of the arts, or the promotion of useful knowledge' was reinforced by the loss of key elements of its leisure infrastructure and the problems in establishing new cultural institutions in the town. But here, perceptions were often more important than reality, and the line of reasoning increasingly ran in the opposite direction.…”
Section: Conclusion: Leisure Luxury and Perceptions Of Politenessmentioning
confidence: 99%
“…63 There is thus a growing dissonance between the reports of metropolitan-inspired travel writers and the array of goods and services, institutions and improvements found in many residential leisure towns. In a way, this was part of the problem.…”
Section: Conclusion: Leisure Luxury and Perceptions Of Politenessmentioning
confidence: 99%
“…Klein further associated the term 'manners' with a person's choice of taste and fashion. Unlike manners, associating politeness to ways of interacting can be traced to the mode of its application (Sweet, 2002). In another observation, politeness is easily identifiable through aspects such as manners, state governance, politics and architectural designs (Langford, 1989) and its administration marks its utopic essence.…”
Section: Introductionmentioning
confidence: 99%